Religious Communication in the Digital Sphere: Framing Prophet Bushiri's YouTube Sermons - Dada, Ambrose Kolawole (Journal for the study of religion, 2025)
One of the African Pentecostalism scholars, Mookgo Kgatle, has described Prophet Shepherd Bushiri as one who has mastered Pentecostal prophecies and is famous for "Prophet-preneurship". This study investigates that claim by examining Bushiri's YouTube sermons through the lens of Paul Gee's Critical Discourse Analysis (CDA) framework. The framing theory illumines this study while using ATLAS.ti to code texts into themes. It explores frames in Bushiri's sermons and his dependence on the new media's capacity to expand influence. While CDA is commonly applied to political texts, this research extends its reach to religious discourse, revealing the ideological dimensions embedded in Bushiri's rhetoric. Findings reveal frames such as cultic tendencies, self-promotion, prosperity gospel, and extra-biblical teachings. These frames and the themes that they generate enhance scholarly understandings of the dynamics of digital evangelism and the commodification of religion in the digital world, offering insights into the non-neutrality of some religious narratives. (The term "non-neutrality" is used here to illustrate that religious narratives like every form of communication is designed to achieve a particular aim - intended or otherwise.)